Hippocampal volume in subjects at clinical high-risk for psychosis: A systematic review and meta-analysis. (December 2016) - Walter, Anna; Suenderhauf, Claudia; Harrisberger, Fabienne; Lenz, Claudia; Smieskova, Renata; Chung, Yoonho; Cannon, Tyrone D.; Bearden, Carrie E.; Rapp, Charlotte; Bendfeldt, Kerstin; Borgwardt, Stefan; Vogel, Tobias
Highlights: Magnetic resonance imaging studies of hippocampal volume in clinical high risk patients compared to healthy controls. Clinical high risk patients showed no hippocampal volume reduction. Hippocampal volume cannot be used as a biomarker. This meta-analysis fosters the neurodegenerative hypothesis of hippocampal volume reduction around transition to psychosis. Abstract: Several magnetic resonance imaging studies have reported reductions in hippocampal volume in patients with psychosis. It is unclear whether structural abnormalities predate illness onset. We conducted a detailed, systematic literature search for studies reporting hippocampal volume in subjects with clinical high-risk, compared to healthy controls. The overall sample size comprised 1429 subjects. Meta-analysis revealed no difference for left, but a small, albeit significant, difference for right hippocampal volume, such that clinical high-risk patients had slightly smaller hippocampal volume than healthy controls (g = 0.24, p = 0.0418). Meta-regression indicated a moderating effect of manual tracing approach, due to one outlying site. The small difference on the right side did not remain significant (g = 0.14, 95%CI = [−0.03–0.32], p = 0.11) after removal of this outlier. This meta-analysis suggests that there is no reduction in hippocampal volume before transition to psychosis and hippocampal volume cannot be used as a biomarker in clinical high-risk individuals.